Gardiner and Renner : Perish - Book 3 - Black, Lisa 1963- (Thorndike, Maine : Center Point Large Print, 2018)
"Forensic expert Maggie Gardiner discovers troubling new details about her colleague Jack Renner, a homicide detective with a brutal approach to law and order, when the two infiltrate the cutthroat world of high-stakes finance to solve a murder"--
Keywords: Women forensic scientists -- Fiction; Murder -- Fiction -- Investigation; Large type books; Mystery fiction